2022
DOI: 10.3389/fmed.2022.939776
|View full text |Cite|
|
Sign up to set email alerts
|

Cuproptosis key gene FDX1 is a prognostic biomarker and associated with immune infiltration in glioma

Abstract: Recent studies have found that the protein encoded by the FDX1 gene is involved in mediating Cuproptosis as a regulator of protein lipoylation and related to immune response process of tumors. However, the specific biological function of FDX1 in glioma is currently unclear. To explore the potential function of FDX1, this study explored the correlation between the expression of FDX1 in cancers and survival prognosis by analyzing the public databases of GEPIA and Cbioportal. Immune infiltration was analyzed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Cell-cell communication analysis based on single-cell sequencing helps to reveal the tumor immune microenvironment and changes in the tumor itself [ 51 ]. Previous studies have shown that FDX1 , as a key gene in cuproptosis, is involved in the progression of hepatocellular carcinoma [ 52 ] and glioma [ 53 ] as well as tumor immunity and drug sensitivity [ 54 ]. To investigate the relationship between angiogenesis and cuproptosis in cervical cancer, we identified two types of cells, FDX1 + tumor/epithelial cells and VEGFA + tumor/epithelial cells, and conducted cell-cell communication analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cell communication analysis based on single-cell sequencing helps to reveal the tumor immune microenvironment and changes in the tumor itself [ 51 ]. Previous studies have shown that FDX1 , as a key gene in cuproptosis, is involved in the progression of hepatocellular carcinoma [ 52 ] and glioma [ 53 ] as well as tumor immunity and drug sensitivity [ 54 ]. To investigate the relationship between angiogenesis and cuproptosis in cervical cancer, we identified two types of cells, FDX1 + tumor/epithelial cells and VEGFA + tumor/epithelial cells, and conducted cell-cell communication analysis.…”
Section: Discussionmentioning
confidence: 99%
“…17 FDX1 serves as a regulator of protein lipoylation, mediating cuproptosis, 10 and is intricately linked to the cellular function, immune response, and disease prognosis of tumors. 18,19 It encodes a reductase that is known for reducing Cu 2+ to its more toxic form, Cu 1+ , 10 and exhibits differential expression and modification levels across various tumors. 19 A comprehensive multi-omics pan-cancer study conducted by Xu et al discovered that FDX1 is highly expressed in 15 types of tumors and exhibits low expression in 11 tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…FDX1, a member of the [2Fe‐2S] cluster‐containing ferredoxin family, encodes a small iron–sulfur protein that is integral to the reduction of mitochondrial cytochromes and the synthesis of various steroid hormones 17 . FDX1 serves as a regulator of protein lipoylation, mediating cuproptosis, 10 and is intricately linked to the cellular function, immune response, and disease prognosis of tumors 18,19 . It encodes a reductase that is known for reducing Cu 2+ to its more toxic form, Cu 1+ , 10 and exhibits differential expression and modification levels across various tumors 19 .…”
Section: Discussionmentioning
confidence: 99%
“…FDX1 is a protein involved in cuproptosis localized to the mitochondrial membrane [ 50 ]. Recent studies have identified FDX1 as a regulator of protein lipoylation involved in cellular cuproptosis [ 51 , 52 ]. Additionally, studies have identified FDX1 as a direct target of ES which enhances a distinct form of Cu-dependent cell death [ 53 ].…”
Section: Cuproptosis In Dmmentioning
confidence: 99%